Role of Land Rent and Capital to Income Households in Indonesia - Endang Taufiqurahman (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
The purpose of the study to determine the effect of land rents and capital on incomes and wages in Indonesian households. Then determine whether the use of the dimensions of wages, as well as the dimensions of income in measuring the influence of capital and land rent-toincome households in Indonesia. This study uses the FD method (First Difference). The data used is panel data sourced from IFLS (Indonesian Family Life Survey) which IFLS-3 in the year 2000, and IFLS-4 in the year 2007. Research results show that an increase in the rent of agricultural land causes decreased significantly to income or household wage in Indonesia. The increase in capital causes a significant slowdown in total household income and wages Indonesia.